Tuvan-Khakass lexico-semantic correspondences in verbs of behavior - Chertykova, Maria D. (The New Research of Tuva, 2020)
The article is devoted to identifying Tuvan-Khakass lexico-semantic correspondences of verbs of behavior. We provide structural and semantic description and clarification of their semantic and cognitive characteristics. In these two languages, in contrast to other classes of verbs, verbs of behavior are quite numerous (220 words in Tuvan, and 277 in Khakass language). Verbs with evaluative, emotional and expressive connotations prevail among these and, accordingly, they are used mainly in colloquial speech. According to our data, are 52 of the verbs of behavior in Tuvan and Khakass languages are lexical equivalents with identical semantics, which accounts for a fourth part of the total. In the course of lexico-semantic analysis of these verbs, we outlined the following types of lexico-semantic equivalents: 1) verbs that are absolutely identical in their semantic and grammatical characteristics; 2) verbs with partial semantic or grammatical differences; and 3) verbs which look similar, but have significant semantic differences. The ratio of Tuvan-Khakass lexical equivalents throughtout these three types is uneven, with most of them belonging to the first type. Almost all have an identical grammatical structure, i.e. common roots and the same derivational indicators. Their semantic structures, including subsequently developed figurative meanings, also coincide. The case of lexical and semantic correspondences between verbs of behavior helped us demonstrate the most influential factor contributing to an expansion of the semantic field of lexemes within a particular language, and thereby to a divergence of closely related languages, is their polysemy and, accordingly, wider combinatorial capabilities. The verbs examined in the article have their lexical and semantic correspondences in other Turkic languages, which opens a prospect for future comparative studies.